2011
DOI: 10.1016/j.febslet.2011.04.070
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin 2 fromEscherichia coliis not involvedin vivoin the recycling process of methionine sulfoxide reductase activities

Abstract: a b s t r a c tThioredoxins (Trx) 1 and 2, and three methionine sulfoxide reductases (Msr) whose activities are Trx-dependent, are expressed in Escherichia coli. A metB 1 trxA mutant was shown to be unable to grow on methionine sulfoxide (Met-O) suggesting that Trx2 is not essential in the Msr-recycling process. In the present study, we have determined the kinetic parameters of the recycling process of the three Msrs by Trx2 and the in vivo expression of Trx2 in a metB 1 trxA mutant. The data demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…This system is ''leaky,'' and even under non-inducing conditions there is a basal expression level from the T7 promoter (see Experimental Procedures for details), which is sufficient to compensate the growth deficiency of the E. coli Trx À strain with the plasmid encoding for the gene of E. coli thioredoxin 1 (Figure 2A). This suggests that the basal expression level leads to thioredoxin concentrations within the complemented E. coli Trx À strain comparable to the normal thioredoxin concentration within E. coli ($10 2 mM) (Jacob et al, 2011).…”
Section: E Coli Strains Used In This Workmentioning
confidence: 87%
“…This system is ''leaky,'' and even under non-inducing conditions there is a basal expression level from the T7 promoter (see Experimental Procedures for details), which is sufficient to compensate the growth deficiency of the E. coli Trx À strain with the plasmid encoding for the gene of E. coli thioredoxin 1 (Figure 2A). This suggests that the basal expression level leads to thioredoxin concentrations within the complemented E. coli Trx À strain comparable to the normal thioredoxin concentration within E. coli ($10 2 mM) (Jacob et al, 2011).…”
Section: E Coli Strains Used In This Workmentioning
confidence: 87%
“…To regain their reductase activity, MsrAs use reducing pathways (35), such as the Trx/TrxR pathway, which is used by most organisms to maintain a reducing environment within cells. Highlighting the importance of the Trx reducing pathway, Trx deletion mutants of Met auxotrophs of E. coli (36) and yeast (37) are incapable of using Met-SO as a Met source. In this study, we have shown that Cd-MsrA is also coupled to the Trx/ TrxR pathway, by monitoring NADPH consumption in a coupled enzyme assay.…”
Section: Discussionmentioning
confidence: 99%
“…8B), further confirming that the Mrx1/Mtr/MSH system is not operative under normal conditions. In E. coli, the GSH/Grx/GR system cannot supply the Trx/TrxR system for the regeneration of the MsrA activity (53), as a Met-auxotrophic E. coli strain cannot grow in the presence of MetO when the genes coding for Trx1 and Trx2 are inactivated (24). However, it is technically difficult to investigate whether the Mrx1/Mtr/MSH system could supply the Trx/TrxR system, because the trx gene in C. glutamicum seems to be essential, and it cannot be deleted (20).…”
Section: Discussionmentioning
confidence: 99%